Effect Of Enrofloxacin Administration On Haematological Profile In Broiler Chicken- A Safety Pharmacology Study - Kumar , V. Suresh; Chandra, G. Sarath; Ramesh, J.; Vairamuthu, S.; Thejomoorthy, P.; Hariharan , P. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
A safety pharmacological trial was conducted to investigate the effect of enrofloxacin on haematological profile after pulsed water medication in broiler chicken, at therapeutic dose 10 mg/ kg body weight through drinking water for five consecutive days in accordance with the FDA approved norms. There was no significant (p>0.05) changes in haemtological parameters except significant (p>0.05) elevation of heterophils on 1st and 3rd day of post treatment and a significant (p>0.05) decrease in lymphocyte count . The results of the present study suggest that the reduction in the lymphocyte count at therapeutic dose of enrofloxacin may have influence on the immune response of the birds.